Peran Work-Life Balance dalam Memediasi Pengaruh Beban Kerja terhadap Stres Kerja Karyawan : (Studi pada Perusahaan Umum Daerah Air Minum Tirta Sewakadarma Denpasar) - Putu Dian Kartika; I Gede Riana (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study aims to analyze the role of work-life balance in mediating the effect of workload against employee work stress of Perusahaan Umum Daerah Air Minum Tirta Sewakadarma Denpasar. This study used a sample of 149 employees. The method used in this research is a survey method with questionnaire and interview techniques. The data that has been collected is analyzed using path analysis inferential statistical analysis tools. The results showed that workload has a significant positive effect on work stress. Workload has a significant negative effect on work-life balance. Work-life balance has a significant negative effect on job stress. Work-life balance mediates the effect of workload on work stress. The implications of this study prove the theory of The Job Demands-Control Model and its relation to the research variables. This research also offers the benefits of work-life balance and workload management on work stress.